The Effect of Using Game on Students' Motivation in Learning Vocabulary - Alwan Faiz; Leroy Holman Siahaan (Tarbiatuna: Journal of Islamic Education Studies, 2022)
This study focuses on the effect of using stimulant play and word learning hard to remember a new word. The purpose of this study was to describe the motivations of students learning pre-game learning, to explain the motivations of students learning pre-game play, to explore the significant impact of using quiz games words. The research method used in this study is numerical. This type of test is an experimental test. In addition, the test sample included 92 students. It consisted of an experimental class of 48 students as well as a management class of 46 students. During the data collection, the researcher used the research paper to determine the motivation for learning English and speaking in data collection. To analyze the data, the researcher used a t-test method. The score of the test class before using Whispering Game is 64 and the score after using Whispering Game is 85. Currently, the score of the class in the test is 75,52 In addition, the t count score is greater than table (5.46> 1.684).